2012
DOI: 10.1590/s0100-879x2012007500115
|View full text |Cite
|
Sign up to set email alerts
|

Mutation and genomic amplification of the PIK3CA proto-oncogene in pituitary adenomas

Abstract: The tumorigenesis of pituitary adenomas is poorly understood. Mutations of the PIK3CA proto-oncogene, which encodes the p110-α catalytic subunit of PI3K, have been reported in various types of human cancers regarding the role of the gene in cell proliferation and survival through activation of the PI3K/Akt signaling pathway. Only one Chinese study described somatic mutations and amplification of the PIK3CA gene in a large series of pituitary adenomas. The aim of the present study was to determine genetic alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 37 publications
0
26
0
2
Order By: Relevance
“…Another study examined PIK3CA mutations and genomic amplifications in 33 PAs including ACTH-, GH-, PRL-producing, and NFPAs, and found that PIK3CA mutations were evident in 12.1% of tumors including one noninvasive ACTH tumor. Genomic amplification (defined as copy number R4) was found in 21.2% of cases (Murat et al 2012).…”
Section: Analysis Of the Rtk/pi3k/akt/mtor Pathways In Pamentioning
confidence: 99%
“…Another study examined PIK3CA mutations and genomic amplifications in 33 PAs including ACTH-, GH-, PRL-producing, and NFPAs, and found that PIK3CA mutations were evident in 12.1% of tumors including one noninvasive ACTH tumor. Genomic amplification (defined as copy number R4) was found in 21.2% of cases (Murat et al 2012).…”
Section: Analysis Of the Rtk/pi3k/akt/mtor Pathways In Pamentioning
confidence: 99%
“…Regarding somatic pathogenic variants, until recently, only stimulatory guanine nucleotide (GTP)-binding protein alpha (GNAS) pathogenic variants were known to be causally related to somatotropinoma pathogenesis in a sizeable proportion of cases (16,17). Current genomic techniques allowed the identification of other frequently recurrent somatic genetic alterations -phosphatidylinositol 3 kinase alpha subunit (PIK3AC) gene in various types of pituitary adenomas (18,19) and ubiquitin-specific protease 8 (USP8) (20,21) and USP48 gene pathogenic variants in corticotropinomas (22).…”
Section: Introductionmentioning
confidence: 99%
“…Constitutive activation of the PI3K-AKT-mTOR signaling cascade is also a feature of pituitary adenomas, and is secondary to mutations or amplification of PI3KCA (10,11) or to overexpression of PI3K (12). NFPAs also display activation of the PI3K-AKT-mTOR pathway (13).…”
Section: Introductionmentioning
confidence: 99%